Between urgent and lifelong matters: overweight children's voices on health promotion pedagogies. Issue 6 (2nd November 2019) - From, Ditte-Marie
ABSTRACT: This article addresses the learner perspective on being overweight by listening to 39 Danish overweight children aged 8–13 years. In accordance with the existing critique of the 'obesity epidemic' and medico-scientific discourses around food and exercise, this article explores how new health imperatives shape overweight children's self-narratives. Health pedagogical activities in Denmark are between urgent and lifelong approaches to achieving health, and the article presents overweight children's voices on having to learn new health behaviour in between these two schisms. From a social constructionist and post-structuralist perspective, the analysis demonstrates how the children both subscribe to discourses of discipline and control over health actions, as well as legitimate narratives of having to adjust, accommodate and negotiate health challenges to everyday life practices. The article addresses what can be learnt from listening to overweight children's voices in the context of performing meaningful health pedagogies.